BIMG-23. SINGLE-VOXEL VERSUS MULTI-SLICE MRSI IN PATIENTS WITH GLIOMA ON A KETOGENIC DIET INTERVENTION. (25th March 2021) - Munjapara, Vasu; Kamson, David; Berrington, Adam; Strowd, Roy; Schreck, Karisa; Barker, Peter
Abstract: BACKGROUND: Ketogenic diet therapies (KDTs) may be beneficial by exploiting glioma metabolic vulnerabilities. The GLioma modified Atkins-based Diet study (GLAD; NCT02286167) evaluated systemic and cerebral (MR spectroscopy) biomarkers to determine the feasibility and biological effects of a KDT in glioma patients. While we observed metabolic changes in tumor and normal brain after KDT using single-voxel MRS (SV-MRS), optimal voxel placement was not always achieved. AIMS: We performed an exploratory analysis comparing cerebral metabolite changes using multi-slice MRSI (MS-MRSI) versus SV-MRS acquisition. METHODS: We evaluated four patients from the GLAD study (mean age 39years; 2 female, 3 AA IDH-mutant, 1 GBM IDH-wildtype) who underwent MRS at baseline and following eight weeks of KDT. SV-MRS (sLASER, TR/TE 2.2s/34ms) was acquired from a 2x2x2cm voxel placed in the residual tumor and the contralateral homologous brain. MS-MRSI was acquired with a multi-slice spin echo sequence (TR/TE 3.6/144ms, 4 slices, nominal resolution 13x7x7mm, SENSE factor 3) and maps of total choline (tCho), total N-acetyl-aspartate (tNAA), and lactate (Lac) were reconstructed and normalized relative to creatine. Metabolite levels were measured on the MS-MRSI maps using a region of interest placed in the same areas studied with the SV-MRS. RESULTS: Lesional tCho and tNAA levels showed strong correlation between SV-MRS and MS-MRSI both at baseline (Pearson's r=0.92 and 0.97, respectively) and after 8 weeks of KDT (r=0.96 and 0.84, respectively). tCho and tNAA correlated less robustly between SV-MRS and MS-MRSI in the contralesional region (r=0.56–0.96). Lesional Lac was significantly lower after KDT (1.01±0.48 versus 0.59±0.24, paired t-test p=0.02). CONCLUSIONS: While SV and MS-MRSI provided generally concordant lesional results, MS-MRSI offers added potential to map regional variations not captured by SV-MRS and thus may better define the control regions. MS-MRSI detected a decrease in tumoral lactate levels following study intervention, suggesting KDT-related changes in tumoral energy metabolism.